Hepatic Venous Outflow Tract Obstruction in Patient with Ulcerative Colitis: A Case Report - Bassi , Nitesh; Shah, Aakash; Mittal, Ishan; Parihar , Shishirendu; Tiwari , Anurag; Kumar, Vinod; Shukla, S. K.; Dixit, V. K.; Yadav , Devesh Prakash (Medical Research and Its Applications Vol. 5, 2024)
The present study reports a case of a patient with UC and CMV colitis, complicated by the development of HVOTO. Patients with inflammatory bowel disease (IBD) are prone to many extra-intestinal manifestations, amongst which the risk for thrombo-embolic complications is one, but hepatic vein thrombosis has been reported as a rare extra-intestinal complication of UC. We report a case of a 23-year-old female diagnosed with Hepatic Venous Outflow tract obstruction (HVOTO) with ulcerative colitis (UC) with Cytomegalovirus (CMV) Colitis. HVOTO with UC is a very rare entity, to the best of our knowledge there have been only a few published case reports of HVOTO with UC. Our patient presented with fever, bloody stools with tenesmus, colicky abdominal pain from the last 6 months, and pedal edema with abdominal distention from the last 2 months. Sigmoidoscopy and biopsy were done on presentation which was suggestive of active ulcerative colitis with CMV colitis. Color Doppler of the spleno-portal axis was done suggestive of HVOTO. The patient was started on Ganciclovir, Mesalamine, and anticoagulants and was subjected to balloon angioplasty after which anticoagulants were continued. The patient has been followed up for 6 months now and is doing well. There should be a high level of suspicion for HVOTO in patients with IBD presenting with ascites, dilated veins and tender hepatomegaly.